Cars - Morse, Jenifer Corr. (Woodbridge, CT : Blackbirch Press, 2001)
Provides photographs and descriptions of ten of the fastest cars ever made, including the Lamborghini Diablo, the Corvette Z06, and the Dodge Viper.
Includes bibliographical references (p. [24]) and index.
5.9.
5.9
3-6
Keywords: Automobiles -- Juvenile literature; Automobiles; Automobiles